Marketing Strategy of Hajj Savings Products at PT. Bank Jabar Banten Syariah Majalengka Branch Office - Novayanti, Deasy; Mujiaty, Yulia; Wijaya, Darma; Nurjanah, Siti; Tusriah, Ika (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Bank Jabar Banten Syariah is a company with a service sector, namely banking. Its production does not create goods but sells fund products, savings, credit and other service services. One of the products at Bank Jabar Banten Syariah is the iB Maslahah Hajj Savings which is a special savings for collecting funds according to Sharia for those who want to go on Hajj. The purpose of this Final Assignment is to find out the marketing strategy of the iB Maslahah Hajj Savings Product, the obstacles and solutions provided to face the obstacles in marketing the iB Maslahah Hajj Savings Product. The data collection method in the preparation of the Final Assignment is the observation method, interview, documentation with the analysis method using qualitative descriptive. The marketing strategy used is in accordance with the 4P marketing mix theory, namely, product, price, place, promotion. The obstacles faced in marketing the iB Maslahah Hajj Savings product are that prospective hajj pilgrims have a less than good mindset, the long waiting list for hajj departure, the increase in hajj costs, the decreasing level of trust, and the large number of umrah travel. The solution that has been implemented by PT. Bank Jabar Banten Syariah in facing the obstacles in marketing the iB Maslahah Hajj Savings product is to always conduct evaluations, carry out Islamic propagation, provide extra services to customers, cooperate with other institutions, and market products via online media.